Asymptomatic presentation of diffuse large B-cell lymphoma as isolated submental lymphadenopathy - Sahoo, Kalpit K.; Mani, Kanika; Singla, Rajveer; Arora, Bhavinder K.; Mahipal; Pal, Naresh (International Surgery Journal, 2024)
Non-Hodgkin lymphoma (NHL) is the most common type of lymphoma, Diffuse larger B-cell lymphoma (DLBCL) being most common type of NHL. Patients usually present at later stage with b-symptoms, lymphadenopathy and organomegaly. Isolated asymptomatic lymphadenopathy is a rare presentation. A 50-year-old female presented with complaints of swelling in the sub mental region. It increased in size over 1month without any associated local or systemic symptoms. On examination a firm, non-tender, mobile swelling of around 2×1.5 cm was present at sub mental region. Abdominal examination revealed no organomegaly. Blood picture- HB- 9.7 gm/dl, TLC- 5200/mm3, neutrophils/ lymphocytes/ eosinophil/ basophils-43.4/44.4/5.1/0.4 and Platelets-2.41 lakhs/mm3. Ultrasonography study was suggestive of necrotic lymph node. Fine needle aspiration cytology demonstrated nonspecific reactive lymphadenitis. After routine pre-operative workup patient was taken up for lymph node excision in elective OR under general anesthesia and the excised lymph node was sent for biopsy. A histopathological diagnosis of diffuse large B-cell lymphoma was made and confirmed with Immunohistochemistry (IHC), (CD20-diffuse positive; CD3-focal positive; Cyclin D-negative; BCL6-positive; CD10- focally positive). Post-operative hospital stay was uneventful. Our case was atypical with asymptomatic presentation with isolated lymphadenopathy with suspicious lymphocytosis. Diagnosis was only possible by histopathology.